2021
DOI: 10.1007/s10926-020-09956-1
|View full text |Cite
|
Sign up to set email alerts
|

Does it matter what your reasons are when deciding to disclose (or not disclose) a disability at work? The association of workers’ approach and avoidance goals with perceived positive and negative workplace outcomes

Abstract: Deciding whether to disclose a disability to others at work is complex. Many chronic mental and physical health conditions are associated with episodic disability and include times of relative wellness punctuated by intermittent periods of activity limitations. This research draws on the disclosure processes model to examine approach and avoidance disclosure and non-disclosure goals and their association with perceived positive and negative workplace outcomes. Participants were 896 employed individuals (57.7% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Issues of workplace disclosure of a disability and accommodation needs are receiving increased attention in disability research. 21 , 22 , 32 , 33 , 34 , 35 , 36 , 37 They highlight that challenges encountered by people living with a disability go beyond the symptoms and limitations created by health conditions, and revolve around perceptions of support, concerns about reprisals if a disability is disclosed, and other psychosocial work factors. 21 , 35 , 38…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Issues of workplace disclosure of a disability and accommodation needs are receiving increased attention in disability research. 21 , 22 , 32 , 33 , 34 , 35 , 36 , 37 They highlight that challenges encountered by people living with a disability go beyond the symptoms and limitations created by health conditions, and revolve around perceptions of support, concerns about reprisals if a disability is disclosed, and other psychosocial work factors. 21 , 35 , 38…”
Section: Discussionmentioning
confidence: 99%
“…Workers living with a disability will report significantly different work context and job conditions than workers with no disability. 21 , 22 , 23 This includes less income, less job control, being less willing to share work-related support needs, and greater job stress and perceived job lock.…”
Section: Introductionmentioning
confidence: 99%
“…Physical disability is the most common reason to exit the workforce before age 60 55 . Further, many workers do not choose to disclose their disability or impairment to supervisors and/or coworkers; 22,56 thus, workplace‐level interventions, versus individually tailored interventions, may positively impact more workers without requiring disclosure 57 . Moreover, workplace‐level improvements in these factors may benefit all workers, whether they have a disability or not 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are a number of episodic physical and mental health conditions that have intermittent symptoms and are largely invisible to others, which could benefit from the types of accommodations described in this study on depression (e.g., Inflammatory Bowel Disease, anxiety disorders). Ongoing research by members of our team have revealed the need for similar accommodations and concomitant challenges in implementing such accommodations (Gignac et al, 2021a;Gignac et al, 2021b;Van Eerd et al, 2020). Workplace parties often consider workplace culture to be an important element in the accommodation of episodic health conditions (Corbière et al, 2016;Corbière et al, 2014;Gignac et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%